An association between Helicobacter pylori infection and cognitive function in children at early school age: a community-based study - Alpert Gershon; Akawi Ashraf; Ornoy Asher; Muhsen Khitam; Cohen Dani (BMC, 2011)
Abstract Background H. pylori infection has been linked to iron deficiency anemia, a risk factor of diminished cognitive development. The hypothesis on an association between H. pylori infection and cognitive function was examined in healthy children, independently of socioeconomic and nutritional factors. Methods A community-based study was conducted among 200 children aged 6-9 years, from different socioeconomic background. H. pylori infection was examined by an ELISA kit for detection of H. pylori antigen in stool samples. Cognitive function of the children was blindly assessed using Stanford-Benit test 5th edition, yielding IQ scores. Data on socioeconomic factors and nutritional covariates were collected through maternal interviews and from medical records. Multivariate linear regression analysis was performed to obtain adjusted beta coefficients. Results H. pylori infection was associated with lower IQ scores only in children from a relatively higher socioeconomic community; adjusted beta coefficient -6.1 (95% CI -11.4, -0.8) (P = 0.02) for full-scale IQ score, -6.0 (95% CI -11.1, -0.2) (P = 0.04) for non-verbal IQ score and -5.7 (95% CI -10.8, -0.6) (P = 0.02) for verbal IQ score, after controlling for potential confounders. Conclusions H. pylori infection might be negatively involved in cognitive development at early school age. Further studies in other populations with larger samples are needed to confirm this novel finding.